A Study on History and Development of Bengali Language: Exploring the Ancient Origins and Impact of Bengali Language (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bengal was an extremely antiquated focal point of Aryan settlement in India. The pre-noteworthy kingdom of Pragjyotiṣ, which reached out from present day Jalpaiguri to the woodlands of Assam, was one of the most punctual Aryan provinces in this nation. 'Vanga' is specified in the Aitereya Āraṅyaka and successive references to this land are found in the incredible sagas—the Rāmāyaṅa and the Mahābhārata. As indicated by Manu, Bengal framed a piece of the Aryyāvarta. The two extraordinary saints of the Dwāpara yuga, who are said to have been the sworn adversaries of Çri Kriṣṅa—the incredible upholder of Brahmanic power, were (1) Jarāsandha, the King of Magadha and (2) Pouṅdraka Vāsu Deva, the King of Pānduā in Bengal, and them two driven expeditions to Dwaraka to subvert the power of Kriṣṅa.